Pancreaticoduodenectomy is justified in a subset of elderly patients with pancreatic ductal adenocarcinoma: A population-based retrospective cohort study of 4, 283 patients. (May 2018) - Lu, Lili; Zhang, Xianbin; Tang, Guanglin; Shang, Yuru; Liu, Peng; Wei, Yushan; Gong, Peng; Ma, Li
Abstract: Background: The survival benefit of pancreaticoduodenectomy (PD) in elderly patients with pancreatic ductal adenocarcinoma (PDAC) is still unclear. Methods: Data pertaining to elderly (age ≥75 years) and younger (age <75 years) patients with potentially curable PDAC who underwent pancreaticoduodenectomy in the period 2004–2013 were extracted from the Surveillance, Epidemiology, and End Results database. The Cox proportional hazards model and stratified Kaplan-Meier survival analyses were performed. Results: A total of 4283 patients (3256 younger patients and 1027 elderly patients) were included. On multivariate analysis, advanced age (age ≥75 years) was not found to be an independent risk factor for diseases specific survival (DSS). Survival analysis disaggregated by gender, tumor size, American Joint Committee on Cancer stage, and tumor differentiation showed comparable DSS in younger and elderly patients (log-rank test). Among patients with poorly-differentiated or undifferentiated tumors, those in the elderly age-group experienced shorter DSS as compared to that of younger patients (poorly-differentiated: elderly vs. younger, 32.779 months vs. 42.198 months, P  = 0.043; undifferentiated: elderly vs. younger, 17.500 months vs. 43.028 months, P  = 0.210). However, PD was still warranted for elderly patients with poorly-differentiated tumors (surgery vs. without surgery, 32.779 months vs. 11.490 months, P  < 0.001). Patients with undifferentiated tumors experienced a non-significant survival benefit after PD (surgery vs. without surgery, 17.500 months vs. 11.699 months, P  = 0.330). Conclusions: Advanced age (age ≥75 years) is not an independent risk factor for DSS. PD is justified in a subset of elderly PDAC patients; however, it should be performed in a high-volume center to minimize the risk of post operative complications. Future studies should explore individualized treatment strategies for elderly patients with undifferentiated tumors. Highlights: Advanced age (age ≥75 years) is not an independent risk factor for pancreatic cancer-specific survival. Pancreaticoduodenectomy is justified in a subset of elderly patients with pancreatic cancer. In the future individualized treatment strategies for elderly patients with undifferentiated tumors should be well addressed.